Morphometrics of Daucus (Apiaceae): A counterpart to a phylogenomic study - Arbizu Berrocal, Carlos Irvin; Reitsma, Kathleen R.; Simon, Philipp W.; Spooner, David M. (John Wiley & Sons, 2020)
•Premise of study: Molecular phylogenetics of genome‐scale data sets (phylogenomics) often produces phylogenetic trees with unprecedented resolution. A companion phylogenomics analysis of Daucus using 94 conserved nuclear orthologs supported many of the traditional species but showed unexpected results that require morphological analyses to help interpret them in a practical taxonomic context. •Methods: We evaluated character state distributions, stepwise discriminant analyses, canonical variate analyses, and hierarchical cluster analyses from 40 morphological characters from 81 accessions of 14 taxa of Daucus and eight species in related genera in an experimental plot. •Key results: Most characters showed tremendous variation with character state overlap across many taxa. Multivariate analyses separated the outgroup taxa easily from the Daucus ingroup. Concordant with molecular analyses, most species form phenetic groups, except the same taxa that are problematical in the molecular results: (1) the subspecies of D. carota, (2) D. sahariensis and D. syrticus, and (3) D. broteri and D. guttatus. •Conclusions: Phenetic analyses, in combination with molecular data, support many Daucus species, but mostly by overlapping ranges of size and meristic variation. The subspecies of D. carota are poorly separated morphologically, are paraphyletic, and all could be recognized at the subspecies rank under D. carota. Daucus sahariensis and D. syrticus are so similar morphologically that they could be placed in synonymy. Combined molecular and morphological data support three species in accessions previously identified as D. broteri and D. guttatus. Molecular and morphological results support the new combination Daucus carota subsp. capillifolius.